CRISPR/Cas9-mediated endogenous C-terminal Tagging of Trypanosoma cruzi Genes Reveals the Acidocalcisome Localization of the Inositol 1,4,5-Trisphosphate Receptor - Lander, Noelia (J Biol Chem, 2016)
Methods for genetic manipulation of Trypanosoma cruzi, the etiologic agent of Chagas disease, have been highly inefficient, and no endogenous tagging of genes has been reported to date. We report here the use of the CRISPR (clustered regularly interspaced short palindromic repeats)/Cas9 (CRISPR-associated gene 9) system for endogenously tagging genes in this parasite. The utility of the method was established by tagging genes encoding proteins of known localization such as TcFCaBP (flagellar calcium binding protein) and TcVP1 (vacuolar proton pyrophosphatase), and two proteins of undefined or disputed localization, the TcMCU (mitochondrial calcium uniporter) and TcIP(3)R (inositol 1,4,5-trisphosphate receptor). We confirmed the flagellar and acidocalcisome localization of TcFCaBP and TcVP1 by co-localization with antibodies to the flagellum and acidocalcisomes, respectively. As expected, TcMCU was co-localized with the voltage-dependent anion channel to the mitochondria. However, in contrast to previous reports and our own results using overexpressed TcIP(3)R, endogenously tagged TcIP(3)R showed co-localization with antibodies against VP1 to acidocalcisomes. These results are also in agreement with our previous reports on the localization of this channel to acidocalcisomes of Trypanosoma brucei and suggest that caution should be exercised when overexpression of tagged genes is done to localize proteins in T. cruzi.